AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA MENUJU GOOD GOVERNMENT GOVERNANCE - Pancawati Hardiningsih; Rachmawati Meita Oktaviani; Ceacilia Srimindarti (JURNAL STIE SEMARANG, 2019)
ADD revenue in Pemalang sub-district of Pemalang district increased from 2015 and 2016 so that the village government must manage accountable village funds in an accountable manner according to Permendagri No. 113 of 2014. The research was conducted by survey method in 13 villages in the Pemalang sub-district of Pemalang district. A total of 72 village officials consisted of village heads, secretaries, treasurers, activity implementation teams, village consultative bodies, and affairs heads. The results showed that the management of village finances at the planning, implementation, administration, reporting and accountability stages did not fully go well according to Permendagri No. 113 of 2014 and Pemup No. 58 of 2015. The planning stage is still oriented toward physical development. The implementation phase is carried out by the activity implementation team that the development activities are orderly and according to standards. At the administration stage, the village treasurer concurrently holds another position so that he does not fully understand the task. In the reporting stage, the village head reports the realization of the use of the budget to the regent through the related SKPD. In the accountability stage, the village head is responsible for the use of the budget to the local government, village consultative bodies, and the community. The results of the management of the Pemalang district village fund allocation have not yet fully implemented the principles of good government governance in the form of transparency and accountability because many village officials have retired and even moved assignments so what happens is a dual position. But routinely followed up with audits from the inspectorate to maintain the quality of the report